WORM INFESTATION AND ASSOCIATED FACTORS IN SCHOOL CHILDREN OF DISTRICT ZHOB, BALOCHISTAN, PAKISTAN - Ali, Umair; Yousaf, Iftekhar; Danish, Syed Hasan; Ahmad, Farah; Hassan, Wafa (Pakistan Journal of Physiology, 2016)
Background: Worm infestation or ‘Soil Transmitted Helminthiasis’ (STH) is a global health problem affecting 3.5 billion people worldwide. STH is the commonest cause of iron deficiency anemia world over, affecting about 1.3 billion people with highest prevalence and morbidity in young children. Anemia in children is associated with growth retardation, delayed motor development, poor cognitive abilities and impaired immune response. The objective of this study was to determine frequency of worm infestation and its causal relationship with iron deficiency anemia and to evaluate factors associated with it. Methods: It was a cross sectional study conducted in district Zhob Balochistan from Apr 2014 to Dec 2014. Our study population was school going children selected according to inclusion and exclusion criteria. A structured questionnaire was administered. Results: Worm infestation was found in 30.6% students. Ascaris was found to be highest in frequency (15.3%) followed by Giardia (4.4%) and Hookworm (3.9%). Out of worm infested students, 87% were anaemic. Conclusion: Most of the children who were affected by worm infestation were anaemic. Pak J Physiol 2016;12(1):18–21